Exploration of Placenta Accreta Spectrum with Placenta Previa and Previous Cesarean Section - Safia Bibi , Saleem Javed , Grannaz Mengel (Journal of Islamic International Medical College)
Objective: To determine the frequency and association of placenta accreta spectrum with placenta previa and previous cesarean sections. Study Design: Retrospective observational study Place and Duration of Study: Obstetrics and Gynaecology Unit-2, Bolan Medical Complex Hospital, Quetta, from 1st January 2023 to 31st December, 2023. Materials and Methods: The clinical records of all pregnant women who had cesarean section for placenta previa and were diagnosed as a case of placenta accreta spectrum were reviewed. Results were calculated and analyzed using Microsoft Excel 13. Data was presented in number and percentages and mean ± SD for qualitative and quantitative variables respectively. Results: Out of 812 cesarean sections performed during the study period, 4.4% were due to placenta previa. The incidence of Placenta Accreta Spectrum (PAS) was 1.4 per 1000 deliveries and 1.6% of total cesarean sections. Most of the cases of placenta previa were type IV (58%). In patients having placenta accrete spectrum, majority of cases were previous three LSCS (38%) and previous four LSCS or more (31%). In all PAS cases, 38.5 % were accrete, 46% were increta and 15.5 % were percreta. Uterine sparing management to achieve haemostasis and preserve fertility was done in 77% of cases. Conclusion: Placenta accreta spectrum is becoming more common due to rise in cesarean sections rates. The risk of PAS and placenta previa can be reduced by decreasing the rate of primary cesarean sections. A multidisciplinary team approach will help to reduce the morbidity and mortality associated with PAS.